2018
DOI: 10.1098/rsbl.2018.0132
|View full text |Cite
|
Sign up to set email alerts
|

The most effective pollinator principle applies to new invasive pollinators

Abstract: G. L. Stebbins' most effective pollinator principle states that when pollinators are not limiting, plants are expected to specialize and adapt to the most abundant and effective pollinator species available. In this study, we quantify the effectiveness of bees, hummingbirds and hawkmoths in a Chilean population of (Phrymaceae), and examine whether flower traits are subject to pollinator-mediated selection by the most effective pollinator species during two consecutive years. Unlike most species in the pollinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…The casual dismissal of the interests of the Mimulus scientific community by these authors is questionable for four reasons. First, the monkeyflower literature encompasses dozens of different Mimulus species across the broader clade (Vickery, 1978;Cooley & al., 2011;Grossenbacher & Whittall, 2011;Grossenbacher & al., 2014;Sobel, 2014;Chase & al., 2017;Kooyers & al., 2017;Peng & al., 2017;Li & al., 2018;Medel & al., 2018;Yuan, 2019). Second, this argument mischaracterizes the size of the research community that studies Mimulus.…”
Section: ■ Reason 3: Mimulus Is Well Recognized In the Scientific Communitymentioning
confidence: 99%
“…The casual dismissal of the interests of the Mimulus scientific community by these authors is questionable for four reasons. First, the monkeyflower literature encompasses dozens of different Mimulus species across the broader clade (Vickery, 1978;Cooley & al., 2011;Grossenbacher & Whittall, 2011;Grossenbacher & al., 2014;Sobel, 2014;Chase & al., 2017;Kooyers & al., 2017;Peng & al., 2017;Li & al., 2018;Medel & al., 2018;Yuan, 2019). Second, this argument mischaracterizes the size of the research community that studies Mimulus.…”
Section: ■ Reason 3: Mimulus Is Well Recognized In the Scientific Communitymentioning
confidence: 99%
“…A recent study demonstrated that the more effective recently arrived invasive Bombus terrestris to a Chilean population of Erythranthe lutea (Phrymaceae) modified selection patterns acting on floral traits (Medel et al, 2018). Our results indicate that the production of seeds by Pollen deposition effectiveness (Dtd).…”
Section: Discussionmentioning
confidence: 63%
“…2013; Medel et al . 2018) in these areas. Muñoz and Arroyo (2004) reported that the presence of vertebrate predators significantly reduces the number of visits of A. melanostoma on flowers of the Andean shrub Chuquiraga oppositifolia D. Don, and Gavini et al .…”
Section: Introductionmentioning
confidence: 90%